An accelerated test method for corrosion resistance of gas diffusion layer

By adding precious metal nanoparticles to the gas diffusion layer to accelerate their corrosion rate, the problem of high corrosion resistance testing time cost in the prior art gas diffusion layer is solved, and rapid and accurate corrosion resistance evaluation is achieved, which improves the performance of fuel cells. and lifespan.

CN118758844BActive Publication Date: 2025-01-10DALIAN MEINIU NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411251720.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-10
Estimated Expiration
2044-09-09

Smart Images

  • Figure CN118758844B_ABST
    Figure CN118758844B_ABST
Patent Text Reader

Abstract

The invention discloses an accelerated test method for the corrosion resistance of a gas diffusion layer, and belongs to the field of hydrogen energy technology. The accelerated test method comprises: when preparing the gas diffusion layer, precious metal nanoparticles are added to a microporous layer to obtain a gas diffusion layer containing precious metal nanoparticles, and the precious metal nanoparticles accelerate the corrosion rate of the gas diffusion layer; the gas diffusion layer containing precious metal nanoparticles is used as a working electrode, a constant potential is applied to the working electrode, and the corrosion current density of the gas diffusion layer containing precious metal nanoparticles is tested over time to evaluate the corrosion resistance of the gas diffusion layer containing precious metal nanoparticles, and then evaluate the corrosion resistance of the gas diffusion layer without precious metal nanoparticles. The accelerated test method of the invention effectively shortens the time for testing the corrosion resistance of the gas diffusion layer and reduces the detection cost; it can be used to quickly and accurately evaluate the corrosion resistance of gas diffusion layers of different manufacturers, different raw materials, and different models.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen energy, and in particular relates to an accelerated testing method for the corrosion resistance of a gas diffusion layer. Background Art

[0002] Hydrogen fuel cells are a type of power generation device that uses hydrogen as fuel to directly convert chemical energy into electrical energy. No harmful byproducts are produced during the reaction, and the energy conversion efficiency can reach 60%~80%. They have the advantages of fast startup, low noise and low temperature operation, and are widely used in transportation, communication equipment, aerospace and portable power sources. The rapid development of hydrogen fuel cell vehicles has greatly promoted the research of proton exchange membrane fuel cells (PEMFC). Proton exchange membrane fuel cells (PEMFC) have the characteristics of zero emissions, high efficiency and energy saving, and are currently the most promising automotive power technology to replace internal combustion engines. The membrane electrode is the core component of the proton exchange membrane fuel cell, which is mainly composed of a proton exchange membrane, a catalyst layer (including a cathode catalyst layer and an anode catalyst layer) and a gas diffusion layer (including a cathode gas diffusion layer and an anode gas diffusion layer). The performance and durability of the membrane electrode directly determine the performance of the fuel cell. However, the durability of PEMFC remains a challenge before its widespread commercialization. Among them, one of the key factors restricting the improvement of battery durability is the corrosion of the electrode carbon support. Based on the requirement for improving battery durability, carbon corrosion has always been a key issue in the field of PEMFC research.

[0003] At present, there are few chemical characterization methods for the corrosion resistance of gas diffusion layer (GDL), among which electrochemical characterization methods are particularly scarce. The currently commonly used test method is to conduct a constant potential test on the GDL and compare its corrosion current density to further determine the corrosion resistance of the GDL; however, the above method has a high time cost, especially in the durability and reliability evaluation process of the GDL; therefore, it is necessary to find an acceleration factor to accelerate the carbon corrosion of the GDL in order to achieve the purpose of improving the test efficiency. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0005] To this end, the present invention provides an accelerated test method for the corrosion resistance of a gas diffusion layer, comprising:

[0006] When preparing the gas diffusion layer, precious metal nanoparticles are added into the microporous layer to obtain a gas diffusion layer containing precious metal nanoparticles, wherein the precious metal nanoparticles accelerate the corrosion rate of the gas diffusion layer;

[0007] The gas diffusion layer containing precious metal nanoparticles is used as a working electrode, a constant potential is applied to the working electrode, and a curve of the change of corrosion current density of the gas diffusion layer containing precious metal nanoparticles over time is tested to evaluate the corrosion resistance of the gas diffusion layer containing precious metal nanoparticles, and then evaluate the corrosion resistance of the gas diffusion layer not containing precious metal nanoparticles.

[0008] Furthermore, the preparation method of the noble metal nanoparticle-containing gas diffusion layer includes: mixing microporous layer carbon with the noble metal nanoparticles to prepare a microporous layer slurry, and coating the slurry on the base layer.

[0009] Furthermore, the noble metal nanoparticles are selected from one or more of nano-platinum, nano-iridium and nano-gold.

[0010] Furthermore, the loading of the noble metal nanoparticles is 0.01 mg / cm 2 ~0.1 mg / cm 2 .

[0011] Furthermore, when the loading amount of the precious metal nanoparticles is the same, the corrosion rates of the nano-platinum-containing gas diffusion layer, the nano-iridium-containing gas diffusion layer and the nano-gold-containing gas diffusion layer are as follows: the corrosion rate of the nano-platinum-containing gas diffusion layer is the fastest, the corrosion rate of the nano-iridium-containing gas diffusion layer is the second fastest, and the corrosion rate of the nano-gold-containing gas diffusion layer is the slowest.

[0012] Furthermore, the noble metal nanoparticles are nano-platinum, and the microporous carbon layer is acetylene black. At this time, the nano-platinum gas diffusion layer is operated at a constant potential of 1.5V for 10 hours, and the nano-platinum loading is increased from 0.01mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 8µA / cm 2 ~60µA / cm 2 Increase;

[0013] The noble metal nanoparticles are nano-platinum, and the microporous carbon layer is acetylene black. At this time, the nano-platinum gas diffusion layer is operated at a constant potential of 0.85V for 10 hours, and the nano-platinum loading is increased from 0.01mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 0.6µA / cm 2 ~6µA / cm 2 Increase.

[0014] Furthermore, the method for evaluating the corrosion resistance of the gas diffusion layer without precious metal nanoparticles comprises:

[0015] According to the time required for the different gas diffusion layers containing precious metal nanoparticles to reach the preset value of the corrosion current density, the corrosion resistance of the different gas diffusion layers containing precious metal nanoparticles is evaluated, and then the corrosion resistance of the different gas diffusion layers without precious metal nanoparticles is evaluated;

[0016] Alternatively, the corrosion resistance of different gas diffusion layers containing precious metal nanoparticles is evaluated according to the corrosion current density of different gas diffusion layers containing precious metal nanoparticles within the same test time, and then the corrosion resistance of different gas diffusion layers not containing precious metal nanoparticles is evaluated.

[0017] Furthermore, the preset value of the corrosion current density is 2µA / cm 2 ~100 µA / cm 2 .

[0018] Furthermore, a constant potential is applied to the working electrode, and the constant potential value is 0.85V vs.RHE~1.5Vvs.RHE.

[0019] Furthermore, the accelerated test method for the corrosion resistance of the gas diffusion layer is used to evaluate the corrosion resistance of the gas diffusion layer of the proton exchange membrane fuel cell, including comparing the corrosion resistance of the gas diffusion layers prepared with different microporous carbon layers.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] The accelerated test method for the corrosion resistance of a gas diffusion layer provided by the present invention is to add precious metal nanoparticles to a microporous layer when preparing the gas diffusion layer, and then test the corrosion resistance of the obtained gas diffusion layer containing precious metal nanoparticles. Compared with the gas diffusion layer without precious metal nanoparticles, the corrosion rate of the gas diffusion layer containing precious metal nanoparticles is accelerated, so that the corrosion resistance of the gas diffusion layer without precious metal nanoparticles can be evaluated more quickly. The accelerated test method for the corrosion resistance of the gas diffusion layer of the present invention can effectively shorten the time for testing the corrosion resistance of the gas diffusion layer and reduce the detection cost on the one hand; on the other hand, it can more quickly and accurately compare the corrosion resistance of gas diffusion layers of different manufacturers, different raw materials, and different models. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a corrosion resistance test curve diagram of a gas diffusion layer containing nano-platinum (platinum added) and a gas diffusion layer not containing precious metal nanoparticles (no platinum added) provided in Example 1 of the present application.

[0023] Figure 2The contact angle comparison diagram of the gas diffusion layer containing nano-platinum (with platinum added) and the gas diffusion layer without precious metal nanoparticles (without platinum added) before and after electrochemical corrosion provided in Example 1 of the present application; wherein, 1# is the gas diffusion layer without precious metal nanoparticles (without platinum added) without electrochemical corrosion, 2# is the gas diffusion layer containing nano-platinum (with platinum added) without electrochemical corrosion, 3# is the gas diffusion layer without precious metal nanoparticles (without platinum added) after electrochemical corrosion, and 4# is the gas diffusion layer containing nano-platinum (with platinum added) after electrochemical corrosion.

[0024] Figure 3 This is a corrosion resistance test curve diagram of a gas diffusion layer containing nano-platinum (platinum added) and a gas diffusion layer not containing precious metal nanoparticles (no platinum added) provided in Example 2 of the present application.

[0025] Figure 4 The contact angle comparison diagram of the gas diffusion layer containing nano-platinum (with platinum added) and the gas diffusion layer without precious metal nanoparticles (without platinum added) before and after electrochemical corrosion provided in Example 2 of the present application; wherein, 1# is the gas diffusion layer without precious metal nanoparticles (without platinum added) without electrochemical corrosion, 2# is the gas diffusion layer containing nano-platinum (with platinum added) without electrochemical corrosion, 3# is the gas diffusion layer without precious metal nanoparticles (without platinum added) after electrochemical corrosion, and 4# is the gas diffusion layer containing nano-platinum (with platinum added) after electrochemical corrosion.

[0026] Figure 5 The nano-platinum (platinum-added) gas diffusion layer, the nano-iridium (iridium-added) gas diffusion layer and the nano-metal nanoparticle-free ( Figure 5 Corrosion resistance test curve of gas diffusion layer (without platinum added) marked in the middle.

[0027] Figure 6 A contact angle comparison diagram of a gas diffusion layer containing no precious metal nanoparticles and a gas diffusion layer containing precious metal nanoparticles before and after electrochemical corrosion provided in Example 3 of the present application; wherein, 1# is a gas diffusion layer containing no precious metal nanoparticles that has not been electrochemically corroded, 2# is a gas diffusion layer containing nano-platinum (plus platinum) that has not been electrochemically corroded, 3# is a gas diffusion layer containing nano-iridium (plus iridium) that has not been electrochemically corroded, 4# is a gas diffusion layer containing no precious metal nanoparticles that has been electrochemically corroded, 5# is a gas diffusion layer containing nano-platinum (plus platinum) that has been electrochemically corroded, and 6# is a gas diffusion layer containing nano-iridium (plus iridium) that has been electrochemically corroded.

[0028] Figure 7 This is a standard curve diagram of Pt loading and corrosion current density in the gas diffusion layer under 1.5V conditions provided in the embodiments of the present application.

[0029] Figure 8 This is a standard curve diagram of Pt loading and corrosion current density in the gas diffusion layer under 0.85V conditions provided in the embodiments of the present application. DETAILED DESCRIPTION

[0030] In order to better understand the above-mentioned technical scheme, the technical scheme of the embodiments of the present application is described in detail below through the accompanying drawings and specific embodiments. It should be understood that the embodiments of the present application and the specific features in the embodiments are detailed descriptions of the technical scheme of the embodiments of the present application, rather than limitations on the technical scheme of the present application. In the absence of conflict, the embodiments of the present application and the technical features in the embodiments may be combined with each other.

[0031] An embodiment of the present invention provides an accelerated testing method for the corrosion resistance of a gas diffusion layer, comprising:

[0032] When preparing the gas diffusion layer, precious metal nanoparticles are added to the microporous layer to obtain a gas diffusion layer containing precious metal nanoparticles. The precious metal nanoparticles accelerate the corrosion rate of the gas diffusion layer. Compared with a gas diffusion layer without precious metal nanoparticles, the corrosion rate of the gas diffusion layer containing precious metal nanoparticles is faster.

[0033] A gas diffusion layer containing precious metal nanoparticles is used as a working electrode, a constant potential is applied to the working electrode, and a curve of the change of corrosion current density of the gas diffusion layer containing precious metal nanoparticles over time is tested to evaluate the corrosion resistance of the gas diffusion layer containing precious metal nanoparticles, and then to evaluate the corrosion resistance of the gas diffusion layer without precious metal nanoparticles.

[0034] The accelerated test method for the corrosion resistance of a gas diffusion layer provided in an embodiment of the present invention comprises the following steps: when preparing the gas diffusion layer, precious metal nanoparticles are added to a microporous layer to obtain a gas diffusion layer containing precious metal nanoparticles; the gas diffusion layer containing precious metal nanoparticles is used for corrosion resistance testing, and then the corrosion resistance of the gas diffusion layer not containing precious metal nanoparticles is evaluated; on the one hand, the time for corrosion resistance testing of the gas diffusion layer is effectively shortened, and the testing cost is reduced; on the other hand, the corrosion resistance of gas diffusion layers from different manufacturers, with different raw materials, and with different models can be compared more quickly and accurately.

[0035] It is understandable that the gas diffusion layer without precious metal nanoparticles is a normal gas diffusion layer, that is, the gas diffusion layer in the prior art. In proton exchange membrane fuel cells, the corrosion resistance of the membrane electrode material is a key factor restricting the durability of the fuel cell. Therefore, by testing the corrosion resistance of the fuel cell diffusion layer and then selecting a gas diffusion layer with good corrosion resistance, the purpose of optimizing the fuel cell performance and extending the life of the fuel cell can be achieved.

[0036] The embodiment of the present invention proposes an accelerated test method for the corrosion resistance of a gas diffusion layer, which can be used for the corrosion resistance test of the gas diffusion layer of a proton exchange membrane fuel cell. When preparing the gas diffusion layer, a certain amount of precious metal nanoparticles can be added to the microporous layer slurry, and the nanoparticles are coated on the hydrophobic carbon paper to obtain a gas diffusion layer containing a certain amount of precious metal. The addition of precious metals will accelerate the corrosion rate of carbon (mainly for the corrosion rate of microporous layer carbon in this application), thereby improving the efficiency of the corrosion resistance test of the gas diffusion layer. At present, the conventional method for testing the corrosion of the gas diffusion layer is: using the traditional three-electrode system, using the gas diffusion layer as the working electrode, under certain potential conditions, by observing the relationship between the corrosion current density and time, a curve is drawn to analyze the degree of corrosion. In this method, the coating slurry of the microporous layer is only composed of polytetrafluoroethylene (PTFE) and microporous layer carbon (conductive carbon black powder). The problems are: ① It takes a long time and the test cost is high, and ② when it comes to comparing the performance of multiple gas diffusion layers, the operation is complicated. In addition, we compared the corrosion resistance of different gas diffusion layers obtained by the accelerated testing method of the embodiment of the present invention with the corrosion resistance of different gas diffusion layers obtained by testing using the above-mentioned conventional method, and found that they were consistent. That is, the accelerated testing method of the embodiment of the present invention can quickly and effectively evaluate the corrosion resistance of different gas diffusion layer materials.

[0037] In some embodiments, the preparation method of the noble metal nanoparticle-containing gas diffusion layer includes: mixing microporous layer carbon with the noble metal nanoparticles to prepare a microporous layer slurry, and coating the slurry on a substrate.

[0038] Specifically, the preparation method of the gas diffusion layer containing precious metal nanoparticles includes: weighing conductive carbon black and the precious metal nanoparticles, mixing them thoroughly, then adding a solvent, stirring and ultrasonicating, and then adding a hydrophobic agent, stirring and ultrasonicating to obtain a microporous layer slurry and coating it on the surface of the base layer hydrophobic carbon paper.

[0039] In some embodiments, the noble metal nanoparticles are selected from one or more of nano-platinum, nano-iridium and nano-gold, and the loading of the noble metal nanoparticles is 0.01 mg / cm 2 ~0.1 mg / cm 2 .

[0040] Our experiments found that adding platinum nanoparticles, iridium nanoparticles or gold nanoparticles to gas diffusion layers made of different microporous carbon layers can accelerate the corrosion rate of the gas diffusion layer. When only the type of precious metal nanoparticles is changed (i.e. the loading amount of precious metal nanoparticles is the same, and other conditions are the same and only the type of precious metal nanoparticles is changed), the corrosion rates of the nano-platinum gas diffusion layer, the nano-iridium gas diffusion layer and the nano-gold gas diffusion layer are as follows: the corrosion rate of the nano-platinum gas diffusion layer is the fastest, the corrosion rate of the nano-iridium gas diffusion layer is the second, and the corrosion rate of the nano-gold gas diffusion layer is the slowest.

[0041] In some embodiments, the noble metal nanoparticles are nano-platinum and the microporous carbon layer is acetylene black. At this time, the nano-platinum gas diffusion layer is operated at a constant potential of 1.5V for 10 hours, and the nano-platinum loading is increased from 0.01 mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 8µA / cm 2 ~60µA / cm 2 Increase; the precious metal nanoparticles are nano-platinum, and the microporous carbon layer is acetylene black. At this time, the gas diffusion layer containing nano-platinum is operated at a constant potential of 0.85V for 10 hours, and the nano-platinum loading is increased from 0.01mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 0.6µA / cm 2 ~6µA / cm 2 Increase.

[0042] Specifically, we experimentally found that the time required for different loadings of precious metal nanoparticles in the gas diffusion layer to reach the same carbon corrosion level is significantly different. Therefore, we explored the relationship between the precious metal (platinum) loading in the microporous layer slurry and the corrosion current density when the microporous layer carbon material is acetylene black. Changing the platinum loading doped in the microporous layer slurry, that is, controlling the platinum loading in the microporous layer (in this application, the precious metal nanoparticles are uniformly mixed with the microporous layer carbon material, and then coated on the substrate, and the platinum loading per unit area of ​​the microporous layer is the same as the platinum loading per unit area of ​​the diffusion layer) is 0.01 mg / cm 2 , 0.02mg / cm 2 , 0.04 mg / cm 2 , 0.06 mg / cm 2 , 0.08 mg / cm 2 , 0.1 mg / cm 2 The nano-platinum gas diffusion layer was operated at a constant potential (1.5V or 0.85V) for 10 h, and a standard curve was drawn with the platinum loading in the microporous layer slurry as the horizontal axis and the corrosion current density value as the vertical axis, so as to more intuitively and conveniently compare the acceleration of the corrosion rate of the gas diffusion layer by different platinum loadings, such as Figure 7 and Figure 8 shown.

[0043] It can be understood that by establishing a standard curve, the relationship between different loadings of precious metals (platinum) in the microporous layer slurry and the corrosion rate of the gas diffusion layer during the operation of the fuel cell can be observed more efficiently, accurately and quickly; while the researchers can infer the corrosion current density value through the precious metal loading, they can also reversely infer the precious metal loading required for the accelerated test through the corrosion current density value; therefore, errors in the experimental process can be effectively avoided to a certain extent and time costs can be shortened.

[0044] In some embodiments, evaluating the corrosion resistance of a gas diffusion layer without precious metal nanoparticles comprises:

[0045] According to the time required for different noble metal nanoparticle-containing gas diffusion layers to reach the preset corrosion current density, the corrosion resistance of different noble metal nanoparticle-containing gas diffusion layers is evaluated, and then the corrosion resistance of different gas diffusion layers without noble metal nanoparticles is evaluated. Among them, the preset corrosion current density is 2µA / cm 2 ~100 µA / cm 2 In general, the corrosion current density is preset to 5µA / cm 2 ~20 µA / cm 2 .

[0046] Alternatively, the corrosion resistance of different gas diffusion layers containing precious metal nanoparticles is evaluated according to the corrosion current density of different gas diffusion layers containing precious metal nanoparticles within the same test time, and then the corrosion resistance of different gas diffusion layers not containing precious metal nanoparticles is evaluated.

[0047] It can be understood that, whether it is a gas diffusion layer containing precious metal nanoparticles or a gas diffusion layer without precious metal nanoparticles (a gas diffusion layer without precious metal nanoparticles is a normal gas diffusion layer), the cause of corrosion is the corrosion of carbon materials. The gas diffusion layer containing precious metal nanoparticles accelerates the corrosion rate of carbon materials, so the corrosion resistance of gas diffusion layers prepared from different microporous carbon layers can be quickly evaluated. The evaluation of the corrosion resistance of different microporous carbon materials or different gas diffusion layers by using a gas diffusion layer containing precious metal nanoparticles is consistent with the evaluation of the corrosion resistance of different microporous carbon materials or different gas diffusion layers by using a gas diffusion layer without precious metal nanoparticles.

[0048] In some embodiments, a constant potential is applied to the working electrode, and the constant potential value is 0.85 V vs. RHE to 1.5 V vs. RHE.

[0049] Specifically, 0.85V corresponds to the normal potential of PEMFC when idling, and is also the highest potential of PEMFC during normal operation. Therefore, setting 0.85V simulates the highest potential during normal operation; 1.5V is the highest potential when the fuel cell has a reverse polarity phenomenon, which rarely occurs. It simulates special working conditions, such as the highest potential reached by the cathode when the potential reverses under conditions such as anode gas shortage. Most gas diffusion layers can operate for a long time under 0.85V conditions. When the potential reaches 1.5V, the corrosion degree of most gas diffusion layers is significantly improved. In the range of 0.85V~1.5V, depending on the selected constant potential value, the corrosion degree of the gas diffusion layer at different potential values ​​can be clearly observed.

[0050] In some embodiments, the accelerated test method for the corrosion resistance of the gas diffusion layer is used to evaluate the corrosion resistance of the gas diffusion layer of a proton exchange membrane fuel cell, including comparing the corrosion resistance of gas diffusion layers prepared with different microporous carbon layers.

[0051] Specifically, we compared the corrosion resistance of different carbon materials including acetylene black, Ketjen black, BP2000, XC-72, etc. by the method of this application. The following is an example of Ketjen black and acetylene black. The nano-platinum gas diffusion layer containing Ketjen black (Pt loading 0.05 mg / cm 2 ), Ketjen black gas diffusion layer without platinum (normal gas diffusion layer of Ketjen black), acetylene black gas diffusion layer containing nano-platinum (Pt loading 0.05 mg / cm 2 ) and acetylene black gas diffusion layer without platinum (normal gas diffusion layer of acetylene black). The results show that after running at a constant potential of 0.85V for 10 hours, the corrosion current density of the gas diffusion layer without platinum of Ketjen black is not significantly different from that of the gas diffusion layer without platinum of acetylene black, while the corrosion current density of the gas diffusion layer containing nano-platinum of Ketjen black is significantly lower than that of the gas diffusion layer containing nano-platinum of acetylene black, indicating that Ketjen black has better corrosion resistance; in sharp contrast to the above results, the gas diffusion layer without platinum of Ketjen black and the gas diffusion layer without platinum of acetylene black can only be seen after running at a constant potential of 0.85V for 100 hours that the corrosion current density of the gas diffusion layer without platinum of Ketjen black is lower than that of the gas diffusion layer without platinum of acetylene black. Therefore, the corrosion resistance of gas diffusion layers of different carbon materials can be quickly evaluated by adding precious metals to the gas diffusion layer.

[0052] Example 1

[0053] An accelerated test method for the corrosion resistance of a PEMFC gas diffusion layer, the specific steps are as follows:

[0054] (1) Step 1, preparing a gas diffusion layer containing precious metal nanoparticles: acetylene black powder and platinum nanoparticles were weighed, mechanically stirred for 30 min to fully mix them, then a certain amount of deionized water was added, stirred and ultrasonicated for 30 min, polytetrafluoroethylene was added, and stirred and ultrasonicated for another 30 min to fully blend them to obtain a slurry, which was then coated on the surface of hydrophobic carbon paper to obtain a gas diffusion layer containing precious metal nanoparticles (i.e., a nano-platinum gas diffusion layer used for corrosion resistance testing); wherein the platinum loading in the nano-platinum gas diffusion layer is 0.05 mg / cm 2 .

[0055] The same method as above was used to prepare a gas diffusion layer without precious metal nanoparticles (a gas diffusion layer without precious metal nanoparticles is a gas diffusion layer without platinum, that is, a normal gas diffusion layer): acetylene black powder was weighed, a certain amount of deionized water was added, and the mixture was stirred and ultrasonically for 30 min. Then polytetrafluoroethylene was added and stirred and ultrasonically for another 30 min to fully blend the mixture to obtain a slurry, which was then coated on the surface of the hydrophobic carbon paper.

[0056] (2) Step 2, corrosion resistance test: The nano-platinum gas diffusion layer prepared in step 1 and the gas diffusion layer without precious metal nanoparticles were placed in a traditional three-electrode system as working electrodes, operated at a potential of 1.5 V, and the relationship between the corrosion current density and time was recorded. The curve was drawn to observe and compare the carbon corrosion degree of the two. Figure 1 As shown; and the corrosion resistance of the two was tested before and after the contact angle test, as shown Figure 2 shown.

[0057] (3) Step 3, determination of corrosion resistance: Analyze and compare the corrosion current density under the same potential conditions and different operating times in the curve.

[0058] Results and Discussion:

[0059] like Figure 1 As shown, the nano-platinum (platinum-added) gas diffusion layer prepared in Example 1 was operated at a potential of 1.5V for 2 hours, and obvious carbon corrosion was observed, while the gas diffusion layer without precious metal nanoparticles (no platinum-added) was operated at a potential of 1.5V for 10 hours, and no obvious carbon corrosion was observed. This shows that the nano-platinum-containing gas diffusion layer accelerates the carbon corrosion rate and greatly shortens the corrosion resistance test time of the gas diffusion layer. In addition, we conducted a corrosion resistance test on a commercial gas diffusion layer (Toray H-055) at a potential of 1.5V and found that it took 10 hours of operation at a potential of 1.5V to observe obvious carbon corrosion.

[0060] We tested the contact angles of the nano-platinum gas diffusion layer and the gas diffusion layer without precious metal nanoparticles prepared in Example 1 before electrochemical corrosion, and the contact angles after electrochemical corrosion for the same period of time. Figure 2 As shown in the figure, after the same period of electrochemical corrosion, the contact angles of the gas diffusion layer containing nano-platinum and the gas diffusion layer without precious metal nanoparticles both show a downward trend, but the degree of decrease of the gas diffusion layer containing nano-platinum is significantly higher than that of the gas diffusion layer without precious metal nanoparticles, and its hydrophobicity is significantly reduced. Therefore, it is believed that the gas diffusion layer containing nano-platinum is more seriously corroded by electrochemical corrosion.

[0061] Example 2

[0062] An accelerated test method for the corrosion resistance of a PEMFC gas diffusion layer, the specific steps are as follows:

[0063] (1) Step 1 is the same as in Example 1.

[0064] (2) Step 2, corrosion resistance test: The nano-platinum gas diffusion layer prepared in step 1 and the gas diffusion layer without precious metal nanoparticles were placed in a traditional three-electrode system as working electrodes, operated at a potential of 0.85 V, and the relationship between the corrosion current density and time was recorded. The curve was drawn to observe and compare the carbon corrosion degree of the two. Figure 3 As shown; and the corrosion resistance of the two was tested before and after the contact angle test, as shown Figure 4 shown.

[0065] (3) Step 3, determination of corrosion resistance: Analyze and compare the curves under the same potential conditions and the corrosion current density reaches 10 µA / cm 2 of running time.

[0066] Results and Discussion:

[0067] like Figure 3 As shown in the figure, the gas diffusion layer containing nano-platinum (platinum added) can reach 10µA / cm after running at a potential of 0.85V for 6000min. 2 The corrosion current density of the gas diffusion layer without precious metal nanoparticles (without platinum) can reach 10 µA / cm2 after running at 0.85V for 20,000 min. 2 This shows that the gas diffusion layer containing nano-platinum accelerates the carbon corrosion rate and greatly shortens the corrosion resistance test time of the gas diffusion layer.

[0068] We tested the contact angles of the gas diffusion layer containing nano-platinum and the gas diffusion layer without precious metal nanoparticles before electrochemical corrosion, as well as the contact angles after electrochemical corrosion for the same time. Figure 4As shown in the figure, under the constant potential condition of 0.85V, the contact angle of the gas diffusion layer without precious metal nanoparticles decreased by 10° after electrochemical corrosion, and the contact angle of the gas diffusion layer containing nano-platinum decreased by 36° after electrochemical corrosion. Through the above data, we found that the hydrophobicity of the gas diffusion layer containing nano-platinum changed more significantly and its corrosion degree was higher.

[0069] Example 3

[0070] An accelerated test method for the corrosion resistance of a PEMFC gas diffusion layer, the specific steps are as follows:

[0071] (1) Step 1, preparing a gas diffusion layer containing precious metal nanoparticles: including a gas diffusion layer containing nano-iridium (iridium-added) and a gas diffusion layer containing nano-platinum (platinum-added); wherein the preparation method of the gas diffusion layer containing nano-iridium is as follows: weighing acetylene black powder and iridium nanoparticles, mechanically stirring for 30 minutes to fully mix them, then adding a certain amount of deionized water, stirring ultrasonically for 30 minutes, then adding polytetrafluoroethylene, stirring ultrasonically for another 30 minutes to fully blend them, obtaining a slurry, and coating the slurry on the surface of hydrophobic carbon paper to obtain a gas diffusion layer containing precious metal nanoparticles (i.e., a nano-iridium gas diffusion layer used for corrosion resistance testing); wherein the iridium loading in the nano-iridium gas diffusion layer is 0.05 mg / cm 2 The preparation method of the nano-platinum-containing gas diffusion layer is the same as that of Example 1.

[0072] Preparation of a gas diffusion layer without precious metal nanoparticles: the same as in Example 1.

[0073] (2) Step 2, corrosion resistance test: The nano-iridium gas diffusion layer, nano-platinum gas diffusion layer and gas diffusion layer without precious metal nanoparticles prepared in step 1 were placed in a traditional three-electrode system as working electrodes, and operated at a potential of 0.85 V for 10 h. The relationship between the corrosion current density and time was recorded, and a curve was drawn to observe and compare the carbon corrosion degree of the three. Figure 5 As shown; and the contact angles of the three before and after the corrosion resistance test were tested, as shown Figure 6 shown.

[0074] (3) Step 3, determination of corrosion resistance: Analyze and compare the curves under the same potential conditions and the corrosion current density reaches 10 µA / cm 2 of running time.

[0075] Results and Discussion:

[0076] like Figure 5 As shown, no precious metal nanoparticles ( Figure 5 The gas diffusion layer (without platinum) can reach 10 µA / cm after running at 0.85 V for 20,000 min. 2The corrosion current density value of the nano-iridium (iridium-added) gas diffusion layer reached 10 µA / cm after running at a potential of 0.85 V for 10,000 min. 2 The corrosion current density of the nano-platinum (platinum-added) gas diffusion layer can reach 10 µA / cm2 after running at a potential of 0.85 V for 6000 min. 2 This shows that both the gas diffusion layer containing nano-iridium and the gas diffusion layer containing nano-platinum can accelerate the corrosion rate of carbon in the diffusion layer, and the precious metal nanoparticles platinum have a more significant effect on accelerating the corrosion of the diffusion layer than the precious metal nanoparticles iridium.

[0077] like Figure 6 As shown in the figure, after electrochemical corrosion, the contact angle of the gas diffusion layer without precious metal nanoparticles decreased by 9°, the contact angle of the gas diffusion layer containing nano-platinum decreased by 35°, and the contact angle of the gas diffusion layer containing nano-iridium decreased by 21°. It can be seen that although the corrosion degree of the gas diffusion layer containing nano-iridium has increased, it is still lower than that of the gas diffusion layer containing nano-platinum. The effect of accelerating the corrosion of the gas diffusion layer containing nano-platinum is more significant.

[0078] In summary, the accelerated testing method provided by the embodiment of the present invention can significantly increase the carbon corrosion rate inside the gas diffusion layer compared to conventional methods, and then accurately and quickly analyze and compare the corrosion resistance of different gas diffusion layers, providing an important technical basis for optimizing the performance of the gas diffusion layer and extending the life of the fuel cell.

[0079] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. An accelerated test method for the corrosion resistance of a gas diffusion layer, characterized in that: include: When preparing the gas diffusion layer, precious metal nanoparticles are added into the microporous layer to obtain a gas diffusion layer containing precious metal nanoparticles, wherein the precious metal nanoparticles accelerate the corrosion rate of the gas diffusion layer; Taking the gas diffusion layer containing precious metal nanoparticles as a working electrode, applying a constant potential to the working electrode, testing a curve of the change of the corrosion current density of the gas diffusion layer containing precious metal nanoparticles over time, evaluating the corrosion resistance of the gas diffusion layer containing precious metal nanoparticles, and further evaluating the corrosion resistance of the gas diffusion layer without precious metal nanoparticles; The noble metal nanoparticles are selected from one or more of nano-platinum, nano-iridium and nano-gold; The loading of the precious metal nanoparticles is 0.01 mg / cm 2 ~0.1 mg / cm 2 .

2. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: The preparation method of the noble metal nanoparticle-containing gas diffusion layer comprises: mixing microporous layer carbon with the noble metal nanoparticles to prepare microporous layer slurry, and coating the microporous layer slurry on the base layer.

3. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: When the loading amount of the precious metal nanoparticles is the same, the corrosion rates of the nano-platinum-containing gas diffusion layer, the nano-iridium-containing gas diffusion layer and the nano-gold-containing gas diffusion layer are as follows: the corrosion rate of the nano-platinum-containing gas diffusion layer is the fastest, the corrosion rate of the nano-iridium-containing gas diffusion layer is the second fastest, and the corrosion rate of the nano-gold-containing gas diffusion layer is the slowest.

4. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: The noble metal nanoparticles are nano-platinum, and the microporous carbon layer is acetylene black. At this time, the gas diffusion layer containing nano-platinum is operated at a constant potential of 1.5V for 10 hours, and the nano-platinum loading is increased from 0.01 mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 8µA / cm 2 ~60µA / cm 2 Increase; The noble metal nanoparticles are nano-platinum, and the microporous carbon layer is acetylene black. At this time, the nano-platinum gas diffusion layer is operated at a constant potential of 0.85V for 10 hours, and the nano-platinum loading is increased from 0.01mg / cm 2 ~0.1 mg / cm 2 Increase, corresponding to the corrosion current density from 0.6µA / cm 2 ~6µA / cm 2 Increase.

5. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: The method for evaluating the corrosion resistance of the gas diffusion layer without precious metal nanoparticles comprises: According to the time required for the different gas diffusion layers containing precious metal nanoparticles to reach the preset value of the corrosion current density, the corrosion resistance of the different gas diffusion layers containing precious metal nanoparticles is evaluated, and then the corrosion resistance of the different gas diffusion layers without precious metal nanoparticles is evaluated; Alternatively, the corrosion resistance of different gas diffusion layers containing precious metal nanoparticles is evaluated according to the corrosion current density of different gas diffusion layers containing precious metal nanoparticles within the same test time, and then the corrosion resistance of different gas diffusion layers not containing precious metal nanoparticles is evaluated.

6. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 5, characterized in that: The corrosion current density is preset to 2µA / cm 2 ~100 µA / cm 2 .

7. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: A constant potential is applied to the working electrode, and the constant potential value is 0.85V vs.RHE~1.5V vs.RHE.

8. The accelerated test method for corrosion resistance of a gas diffusion layer according to claim 1, characterized in that: The accelerated test method for the corrosion resistance of the gas diffusion layer is used for evaluating the corrosion resistance of the gas diffusion layer of a proton exchange membrane fuel cell, including comparing the corrosion resistance of gas diffusion layers prepared from different microporous carbon layers.